What do I really want to know? Self-control to face stress and informative smog. The art of selection - Arenas Iparraguirre, Carlos (1999)
The impact of the technology communicative in societies with peruvian have a effect above the distinct populousness, is imperative of the psychology as science and profession to face of decir situation. It present something reflections from a perspective interdisciplinary and also to sustain something strategy, particulary associate with the necessity of research, where the professionals of the humans sciences will have orient and will orients inside "informative smog" with the which to live daily.